THE INCREASING CAPACITY CAPTURES BUSINESS OPPORTUNITIES FOR GOAT FARMERS - Purbaningsih, Yuli; Helviani, Helviani; Tatra, Afsitin Joan; Jannah, Raodatul; Rahim, Abdul; Handayani, Fitrianti; Rahman, Irsan; Nekstriani, Nekstriani (International Journal of Engagement and Empowerment (IJE2), 2023)
The livestock sector is the most important factor in supporting food security to support sustainable development in Indonesia. The livestock sector is one of the sub-sectors which is a driving force for development, especially in rural areas. Goats are livestock that are widely kept and are well known by the Indonesian people. People like to breed goats because their body size is not too big. Goat farming has an important role in Indonesian livestock as a meat producer to meet domestic needs, and also has the potential to supply the export market. Marketing of goats is very wide open, however there are several problems faced by farmers, namely, the quality of goats is influenced by the type of nutrition/fodder provided and the type of goat itself. Goat farming for rural communities is a side job, but it is mandatory, looking at the condition of the community in Toari District, Kolaka Regency, which shows that every household has at least 7 goats. By increasing the capacity to capture business opportunities for goat breeders, goat breeders can increase their income